CLONING AND EXPRESSION OF CHAETOMIUM THERMOPHILUM XYLANASE 11-A GENE IN PICHIA PASTORIS - Andleeb, S.; Latif, F.; Afzal, S.; Mukhtar, Z.; Mansoor, S.; Rajoka, I. (The Nucleus, 2020)
The various thermophilic fungi like Chaetomium thermophile has potential to secrete xylanase and cellulase enzymes. In the present study eukaryotic expression system of Pichia pastoris (yeast) was used to express xylanase gene. The xylanase (Xyn 11-A) gene was isolated from C. thermophile strain NIBGE-1. Primers were designed to amplify the gene, ligated into P. pastoris pPIC3.5K vector, the resultant recombinant clone pSSZ810 was transformed into the genome of P. pastoris GS115 strain through electroporation. Transformants were selected on yeast peptone dextrose medium (YPD) plates containing antibiotic geneticin (100 mg/mL) upto final concentration of 0.75 mg/mL. The maximum activity of xylanase 2.04 U/mL after incubation of 2 hrs at 50ÂºC was observed in the presence of 100% methanol inducer upto final concentration of 30Î¼L (0.5%) as compared to control. HPLC analysis represented high peak of xylose as compared to control. SDS-PAGE indicated approx. 28 kDa protein of expressed xylanase gene.